Marketplace Selection Based on Product, Price, and Promotion Using the Simple Additive Weighting (SAW) Method - Novi Juliada Lishatriyana; Tety Elida Siregar (Dinasti Publisher, 2023)
The Covid-19 pandemic in Indonesia has an impact on people's spending behavior. Online shopping is an option. On the other hand, business people take advantage of this phenomenon with various marketing strategies. How to choose a marketplace that sells good quality products at low prices is an interesting study to research. The research was conducted on 10 marketplaces. The analytical method used in this research is descriptive quantitative. The analytical tool used in this study uses the Simple Additive Weighting (SAW) method. The results showed that the marketplace with the best products was Zalora. The marketplace with the lowest price is Rarali.com. The marketplace with the most interesting promotions is occupied by Blibli. The marketplace with the best product quality, fairly low prices, and attractive promotions is occupied by Lazada.